Training of Electric Bike Assembly with Lithium Batteries at SMK Muhammadiyah 6 Karanganyar - Paramitha, Tika; Dyartanti, Endah Retno; Widiyandari, Hendri; Jumari, Arif; Nur, Adrian; Inayati, Inayati; Budiman, Anatta Wahyu; Purwanto, Agus (Program studi Teknik Kimia UNS, 2021)
With the increasing development of the battery and electric vehicle industry, student's and teacher's understanding of lithium batteries and skills in assembling electric bikes are very important in competing for jobs in these fields. Educational activities regarding batteries and training on assembling electric bike are carried out at SMK Muhammadiyah 6 Karanganyar, because there were no facilities that support the learning and teaching process about electric vehicles and batteries. The method used in this training is lecture, discussion and practice method. The material presented was about the technology of making lithium batteries and electric bike components. While practical activities include the stages of converting conventional bikes into electric bikes with energy from lithium batteries. This activity shows that participants can understand batteries and can apply batteries to electric vehicles, especially electric bikes.